Roshwald’s Philosophy of Care – the Creative Nature of the Concern (Implications for Sustainable Development) - Bartoszewski, Jakub (Problemy Ekorozwoju, 2015)
The article considers issues connected with Professor Mordecai Roshwald’s philosophical and anthropological thought. It presents important elements of the philosophy of care, focusing on its fundamental concepts such as: appeal, dignity, being-with-you, and being-with-we. It is postulated that these elements may be employed to serve ​​the idea of sustainable development. This has been done on the example of the so-called participation: a. social participation, b. mechanisms for citizen participation.